Is a first acute symptomatic seizure epilepsy? Mortality and risk for recurrent seizure - Hesdorffer, Dale C.; Benn, Emma K. T.; Cascino, Gregory D.; Hauser, W. Allen (Epilepsia (Copenhagen), 2009)
Summary Purpose:  To compare mortality and subsequent unprovoked seizure risk in a population‐based study of acute symptomatic seizure and first unprovoked seizure due to static brain lesions. Methods:  We ascertained all first episodes of acute symptomatic seizure and unprovoked seizure due to central nervous system (CNS) infection, stroke, and traumatic brain injury (TBI). Subjects were residents of Rochester, Minnesota, identified through the Rochester Epidemiology Project’s records‐linkage system between 1/1/55 and 12/31/84. Information was collected on age, gender, seizure type, etiology, status epilepticus (SE), 30‐day and 10‐year mortality, and subsequent episodes of unprovoked seizure. Results:  Two hundred sixty‐two individuals experienced a first acute symptomatic seizure and 148 individuals experienced a first unprovoked seizure, all due to static brain lesions. Individuals with a first acute symptomatic seizure were 8.9 times more likely to die within 30 days compared to those with a first unprovoked seizure [95% confidence intervals (CI) = 3.5–22.5] after adjustment for age, gender, and SE. Among 30‐day survivors, the risk of 10‐year mortality did not differ. Over the 10‐year period, individuals with a first acute symptomatic seizure were 80% less likely to experience a subsequent unprovoked seizure compared with individuals with a first unprovoked seizure [adjusted rate ratio (RR) = 0.2, 95% CI = 0.2–0.4]. Discussion:  The prognosis of first acute symptomatic seizures differs from that of first unprovoked seizure when the etiology is stroke, TBI, and CNS infection. Acute symptomatic seizures have a higher early mortality and a lower risk for subsequent unprovoked seizure. These differences argue against the inclusion of acute symptomatic seizures as epilepsy.